Teaching Speaking by Using Project-Based Learning to the Eighth Grade Students - Ihwan; Nadrum; Anjar Kusuma Dewi; Rofiqoh (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The objective of this research was to determine if Project-Based Learning (PjBL) can improve the speaking ability of eighth-grade students at SMP Negeri 1 Palu. This research applied a quasi-experimental design. The samples consisted of students from class VIII B as the experimental group and class VIII D as the control group, selected through purposive sampling from a population of 349 students across 11 classes. Data were collected from test results (pre-test and post-test) and analyzed statistically. The pre-test score for the experimental class was 36.25, while the post-test score was 70.12, indicating a significant improvement in speaking skills due to the treatment. Additionally, it was found that the class became more engaging and encouraged students' creativity. Hence, teaching using PjBL effectively improves the speaking skills of eighth-grade students at SMP Negeri 1 Palu. The findings of this research suggest that integrating Project-Based Learning (PjBL) into the classroom not only enhances students' speaking abilities but also creates a more engaging and stimulating environment, thereby fostering student creativity and motivation.